PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PT. BFI FINANCE DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Prima Yulianti; Widya Sarminda Utami (Universitas Dharma Andalas, 2019)
PT. BFI Finance is a company engaged in services. Customers who come to PT. BFI Finance will be introduced to the products and services of PT. BFI Finance such as motorized vehicle financing, financing of heavy equipment, trucks and machinery, financing of homes and shop houses and financing the procurement of goods and services. The purpose of this study was to analyze the effect of compensation on the performance of employees of PT. BFI Finance by using work motivation as an intervening variable. The type of research used in this study is to use a quantitative approach using the census method. This research refers to employees of PT. BFI Finance. The sample used in this study amounted to 58 employees. Data collection methods used were questionnaires and library research. The technical data analysis used is partial least square analysis. The results of the study prove that there is a significant and significant effect of Compensation on Employee Performance with Work Motivation as an Intervening Variable